2021
DOI: 10.1002/jcb.30072
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of AFAP1‐AS1 lncRNA impairs cell proliferation and migration by epigenetically promoting DUSP5 expression in pre‐eclampsia

Abstract: As a unique and common obstetric complication of pregnant women, pre‐eclampsia (PE) has been the first leading cause of maternal and perinatal morbidity and mortality in the world. Mounting studies have demonstrated that an abnormality of long noncoding RNA (lncRNA) expression was related to the pathological process of PE. Here, we showed that lncRNA AFAP1‐AS1 was markedly downregulated in pre‐eclamptic placentas. We further investigated the mechanism underlying the regulatory role of AFAP1‐AS1 in PE using hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
2
6
0
Order By: Relevance
“…Our current study showed that expression of DUSP5 is severely repressed in cervical cancer tissues. Consistent with our results, DUSP5 expression in pre-eclampsia inhibits trophoblast proliferation, migration and invasion [ 47 ]. In addition, it has been shown that DUSP5-mediated ERK suppression can serve as a protective mechanism by blocking pulmonary vascular smooth muscle cell proliferation, by preventing pulmonary hypertension and right ventricular cardiac hypertrophy [ 48 ] and by inhibiting inflammation in adipocytes [ 35 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our current study showed that expression of DUSP5 is severely repressed in cervical cancer tissues. Consistent with our results, DUSP5 expression in pre-eclampsia inhibits trophoblast proliferation, migration and invasion [ 47 ]. In addition, it has been shown that DUSP5-mediated ERK suppression can serve as a protective mechanism by blocking pulmonary vascular smooth muscle cell proliferation, by preventing pulmonary hypertension and right ventricular cardiac hypertrophy [ 48 ] and by inhibiting inflammation in adipocytes [ 35 ].…”
Section: Discussionsupporting
confidence: 92%
“…In addition, lncRNA AFAP1-AS1 silencing epigenetically caused the upregulation of DUSP5, thereby restricting trophoblast proliferation and migration in PE. 28 Similarly, in the present study, it was found that SNHG22 was downregulated in PE placentas, and overexpression of SNHG22 promoted migration and invasion of HTR-8/Svneo and JEG-3 cells, while they were inhibited by SNHG22 silencing, which confirmed the contribution of SNHG22 to biological behaviors of trophoblasts.…”
Section: Discussionsupporting
confidence: 86%
“…All placental tissues were washed with sterile saline and stored in liquid nitrogen. The clinicopathological characteristics of healthy pregnant women and PE patients are summarized in Table S1 (published by Zhang et al 54 ). The study protocol was approved by the ethics committee of the First Affiliated Hospital of Nanjing Medical University.…”
Section: Placenta Samples Collectionmentioning
confidence: 99%